Prenatal delineation of a distinct lethal fetal syndrome caused by a homozygous truncating KIDINS220 variant. Issue 12 (10th September 2020) - El‐Dessouky, Sara H.; Issa, Mahmoud Y.; Aboulghar, Mona M.; Gaafar, Hassan M.; Elarab, Ahmed Ezz; Ateya, Mohamed I.; Omar, Heba H.; Beetz, Christian; Zaki, Maha Saad
Abstract: Kinase D‐interacting substrate of 220 kDa ( KIDINS220 ) is a transmembrane protein playing integral role in growth mediating pathways in the nervous and cardiovascular systems. KIDINS220 heterozygous truncating variants that affect the protein's C‐terminus have been associated with a phenotype, so far described only in few unrelated children, including spastic paraplegia, intellectual disability, nystagmus, and obesity. More recently, a homozygous, more N‐terminal truncating variant in KIDINS220 gene was suggested to be associated with enlarged cerebral ventricles and limb contractures in three fetuses from a consanguineous family. We confirm the latter finding by presenting the first detailed prenatal identification of a fetal phenotype associated with novel homozygous deleterious frameshift variant in KIDINS220 gene in a consanguineous healthy Egyptian couple. History of unexplained seven miscarriages and a similar stillbirth were recorded. Prenatal ultrasonography revealed limb contractions and ventriculomegaly; in addition to previously unreported cerebellar anomalies, cardiac anomalies and hydrops fetalis. These findings represent an expansion of clinical and molecular spectrum associated with KIDINS220 variants and broaden our understanding of genotype–phenotype relationships in lethal congenital contractures syndromes and associated severe abnormal embryological development. More generally, our study adds KIDINS220 to the rare group of genes which may cause disease by either of two distinct mutational mechanisms.